Reducing household air pollution exposure to improve early child growth and development; a randomized control trial protocol for the “Poriborton-Extension: The CHANge trial” - Raynes-Greenow, Camille; Billah, Sk Masum; Islam, Sajia; Rokonuzzaman, S. M.; Tofail, Fahmida; Kirkwood, Elizabeth K.; Alam, Ashraful; Chartier, Ryan; Ferdous, Tarana E.; El Arifeen, Shams; Dibley, Michael J.; Homaira, Nusrat; et al. (Current controlled trials in cardiovascular medicine, 2022)
Background Globally, household air pollution (HAP) is a leading environmental cause of morbidity and mortality. Our trial aims to assess the impact of liquefied petroleum gas (LPG) for cooking to reduce household air pollution exposure on child health outcomes, compared to usual cooking practices in Bangladesh. The primary aim is to evaluate if reduced exposure to HAP through the provision of LPG for cooking from early gestation through to age 2 improves child anthropometry, health, and neuro-cognitive developmental outcomes, compared to children exposed to emissions from usual practice. Methods Two-arm parallel cluster randomized controlled trial (cCRT). We will extend the intervention and follow-up of our existing “Poriborton” trial. In a subset of the original surviving participants, we will supply LPG cylinders and LPG stoves (intervention) compared to usual cooking practices and extend the follow-up to 24 months of age. The expected final sample size, for both (intervention and control) is 1854 children with follow-up to 2 years of age available for analysis. Discussion This trial will answer important research gaps related to HAP and child health and neuro-cognitive developmental outcomes. This evidence will help to understand the impact of a HAP intervention on child health to inform policies for the adoption of clean fuel in Bangladesh and other similar settings. Trial registration The Poriborton: Change trial: Household Air Pollution and Perinatal and early Neonatal mortality is registered with the Australian New Zealand Clinical Trials Registry, ACTRN12618001214224, original trial registered on 19th July 2018, extension approved on 23rd June 2021. www.anzctr.org.au .